Standard Serbian Terminological Expressions in Telecommunications and Postal Traffic Created by Borrowing and Translating English Terms - Telebaković Gordana Dimković (Romanian Journal of English Studies, 2018)
The primary purpose of this article is to propose standard Serbian terminological expressions for 140 English telecommunications and postal traffic terms. To achieve this aim, we adopt a synchronic lexico-semantico-translation approach and develop an eight-principle translation and standardisation model. The results of the study clearly show that Anglicisms, synonymous and polysemous terminological units, terminological gaps and imprecise translation terms cause problems. Some solutions are suggested to bridge terminological inaccuracy and to set the standard status of certain Serbian terms.